Pola Tahanan Pentanahan Tower Saluran Udara Tegangan Tinggi (SUTT) 150 KV Sekarputih – Ngoro - Bambang Minto Basuki; Adi Noerhamsyah (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
The electrode rods in the grounding system of the High Voltage transmission tower that are embedded in the ground will experience changes in grounding resistance values ​​over time. If the grounding resistance value increases and exceeds the set standard, which is <10 Ω, then immediate repairs need to be made. This research was conducted on the 150 kV High Voltage transmission tower from Sekarputih to Ngoro using the Earth Tester tool. The purpose of this study was to find the right method to improve grounding resistance on the 150 kV High Voltage tower that has high impedance to comply with the standard. The results of measurements in the field showed that there were 3 towers with high grounding resistance values, which exceeded <10 Ω, which required immediate repairs.